Real time PCR typing of canine parvovirus types in various regions of northern India - KOUR, KARMAN; KAUR, GURPREET; CHANDRA, MUDIT; DWIVEDI, P N (The Indian Journal of Animal Sciences, 2022)
Canine parvovirus (CPV) is a ssDNA virus which has high morbidity in unvaccinated and some vaccinated dogs as well. It is seen to be evolving and has various antigenic types. The present study was aimed to study the prevalence of the antigenic type in northern India by real-time PCR. This study was conducted in 2019 wherein 178 samples (collected from Delhi, Punjab, Jammu, Chandigarh and Assam) available in the Department of Veterinary Microbiology, College of Veterinary Science, Guru Angad Dev Veterinary and Animal Sciences University, Ludhiana were subjected to real time PCR for CPV 2, CPV 2a and CPV 2b. Out of 178 samples, 133 were found to be positive and amongst the three CPV types, CPV 2a was most prevalent. It was also observed that a few samples were positive for more than one antigenic type simultaneously. CPV 2a is most prevalent in the areas under study and a dog can be affected by more than one antigenic type simultaneously. Also, real-time PCR is a sensitive method for the diagnosis of canine parvovirus.